Transfer Pricing Aggressiveness, Thin Capitalization, Political Connections, Financial Performance, and Tax Avoidance: Corporate Governance as a Moderating Variable - Oktania, Yanesti; Putra , Yudi Partama (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to examine transfer pricing aggressiveness, thin capitalization, political connections, financial performance, and tax evasion: corporate governance as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2012-2021 period. The population in this study is the annual report (annual report) consists of 193 companies. The sample technique selected based on certain criteria using purposive sampling was 9 companies.This research is a quantitative research with secondary data. Methods of data collection using the method of literature study and documentation methods. The data analysis technique used was descriptive statistical test, hypothesis testing using panel data regression tools, and moderate regression analysis (MRA) was processed using the STATA 17 program.The results of this study indicate that the results of the partial test prove that transfer pricing aggressiveness has no effect on tax avoidance with a significance value of 0.279 > 0.05, thin capitalization has no effect on tax evasion with a significance value of 0.731 > 0.05, political connections have no effect on tax evasion with a value a significance of 0.861 > 0.05, and financial performance has no effect on tax evasion with a significance value of 0.178 > 0.05. Corporate governance can moderate the relationship between transfer pricing aggressiveness to tax evasion with a significance value of 0.015 <0.05, corporate governance cannot moderate the relationship between thin capitalization and tax evasion with a significance value of 0.631 > 0.05, corporate governance cannot moderate the relationship between political connections to tax evasion with a significance value of 0.317 > 0.05, and corporate governance can moderate the relationship between financial performance and tax evasion with a significance value of 0.009 <0.05. The results of this test indicate that the Adjusted R-squared value is 0.0645 or 6.45%.